Application of endolysin LysSTG2 as a potential biocontrol agent against planktonic and biofilm cells of Pseudomonas on various food and food contact surfaces. (January 2022) - Zhang, Yu; Huang, Hung-Hsin; Duc, Hoang Minh; Masuda, Yoshimitsu; Honjoh, Ken-ichi; Miyamoto, Takahisa
Abstract: The gene encoding LysSTG2, a novel endolysin from Salmonella- lytic bacteriophage STG2, has been cloned, overexpressed, and characterized previously. In this study, LysSTG2 was used to control Pseudomonas aeruginosa and P. putida, which showed high sensitivity to LysSTG2, in bottled water, milk, chicken breast, salmon, and the biofilms formed on the surface of polystyrene resin and stainless steel. In bottled water, LysSTG2 combined with EDTA reduced the viable counts of P. aeruginosa and P. putida by 2.2 log and to lower than the limit of detection, respectively. However, there was no significant decrease in viable counts in pasteurized milk artificially contaminated with these bacteria. Meanwhile, the addition of 1 mg/mL LysSTG2 alone reduced the viable counts of P. aeruginosa and P. putida by 0.6 log in chicken and 1.1 log in salmon samples contaminated with these bacteria, respectively. Further reduction in viable counts in combination with EDTA was not observed. Additionally, a strong effect of LysSTG2 on the removal of P. aeruginosa and P. putida biofilms was observed on the polystyrene resin and stainless steel surfaces, displaying more than 99.9% decrease in viable biofilm cells after 2 h of treatment at 37 °C. The results of this study suggest that LysSTG2 has the potential to control both planktonic and biofilm cells of Pseudomonas . Further investigations are required to optimize and improve the use of the endolysin for application in food and food processing facilities. Graphical abstract: Image 1 Highlights: LysSTG2 was highly effective to planktonic and biofilm cells of Pseudomonas. LysSTG2 effectively killed the P. aeruginosa and P. putida in bottled water, chicken and salmon. LysSTG2 showed strong antibiofilm effects against Pseudomonas on polystyrene and stainless steel.